2018
DOI: 10.1080/13657305.2018.1454539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regulations on technical efficiency of U.S. baitfish and sportfish producers

Abstract: The stringency of the regulatory environment has been shown to negatively affect the growth of aquaculture. A technical efficiency analysis of baitfish/sportfish production in the United States was performed using a stochastic production frontier model and a jointly estimated maximum-likelihood procedure (Frontier 4.1). Determinants of inefficiency were assessed for their relationship to farm efficiency. Mean technical efficiency for U.S. baitfish and sportfish producers was found to be 77%. Several regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 43 publications
5
36
1
Order By: Relevance
“…However, as a producer, the United States did not take part in the aquaculture revolution, and today, it is a minor player, accounting for 0.39% of global production in 2017. There are of course several reasons for this, with tight regulations and high regulatory cost receiving the most attention (Chu, Anderson, Asche, & Tudur, ; Chu & Tudur, ; Engle & Stone, ; Knapp & Rubino, ; van Senten & Engle, ; van Senten & Engle, ). The fact of the matter remains that aquaculture production is not significant in the United States and that the landings of wild fish are stable and unlikely to increase; thus, any increase in seafood consumption in the United States has to be based on imports.…”
Section: Overview Of Landings Imports and Exports And Aquaculture Pmentioning
confidence: 99%
“…However, as a producer, the United States did not take part in the aquaculture revolution, and today, it is a minor player, accounting for 0.39% of global production in 2017. There are of course several reasons for this, with tight regulations and high regulatory cost receiving the most attention (Chu, Anderson, Asche, & Tudur, ; Chu & Tudur, ; Engle & Stone, ; Knapp & Rubino, ; van Senten & Engle, ; van Senten & Engle, ). The fact of the matter remains that aquaculture production is not significant in the United States and that the landings of wild fish are stable and unlikely to increase; thus, any increase in seafood consumption in the United States has to be based on imports.…”
Section: Overview Of Landings Imports and Exports And Aquaculture Pmentioning
confidence: 99%
“…Facility‐level information on compliance costs of regulations are generally lacking but are especially important for industries that are heterogeneous in terms of size (National Center for Environmental Economics, ). To gain a better understanding of the on‐farm economic effects of the implementation of regulations in the United States, van Senten and Engle () found costs on baitfish/sportfish farms to be, on average, $148,554/farm, $7,383/ha, and to constitute 25% of total costs of production. Per‐hectare costs were found to be substantially greater on smaller, when compared to larger, baitfish/sportfish farms and may have contributed to the exodus of small farms from the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Per‐hectare costs were found to be substantially greater on smaller, when compared to larger, baitfish/sportfish farms and may have contributed to the exodus of small farms from the industry. A subsequent analysis showed that regulations decreased farm‐level efficiency as owners and managers were required to spend greater amounts of time on record keeping and reporting and proportionately less time on farm‐level innovation and market development (Kumar, ; van Senten, Dey, & Engle, ). Asche and Roll () and Dresdner and Estay () similarly found that regulatory requirements contributed to farm‐level inefficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research focus remains on economic and societal conflict around resource use, environmental concerns, and potential recreational/leisure conflicts. Much of this information has led to increasingly onerous and costly regulatory response (Abate et al ; van Senten and Engle ). In developed nations, increasing importance is thus being assigned to social license, or “the demands on and expectations for a business enterprise that emerge from neighborhoods, environmental groups, community members, and other elements of the surrounding civil society” (Gunningham et al ).…”
mentioning
confidence: 99%